Infection control in Finnish acute care hospitals 2008 - Kärki, Tommi; Ruutu, Petri; Lyytikäinen, Outi (International Journal of Infection Control, 2011)
Infection control (IC) in hospitals depends on adequate human resources and organization. The aim of the study was to assess the IC resources and activities in Finnish acute care hospitals. A questionnaire covering information on hospital characteristics, IC staff and surveillance activities in 2008 was mailed to all Finnish acute care hospitals. All 57 (100%) hospitals responded. Of the hospitals, 70% had infectious disease specialists and 37% had clinical microbiologists who participated in the IC. Most of the hospitals (88%) had trained IC nurses. The median number of hospital beds per full-time equivalent ICN was 257 (range, 87-770). The IC staff had limited secretarial and IT-support. Most hospitals (95%) had IC committees as well as a link nurse system (96%), and they all implemented incidence surveillance at least in one specialty. In comparison with the results from our previous study in 2000, the ICN to bed ratio has improved (2000: range 394-953 beds/ICN). Now that the situation with IC staff seems better, the focus could be shifted to additional training and an evaluation of the curriculum of the ICNs.